KAJIAN SEDIMEN TRANSPOR DAERAH ALIRAN SUNGAI KRASAK PASCA ERUPSI GUNUNGAPI MERAPI 2010 - , GANI RACHMAN PRAJOTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Sediment is the result of erosion process which occurred in a watershed system. Based on the transportation mechanisms, sediment can be divided into two parts